BIMBINGAN DAN PELATIHAN PENYUSUNAN LAPORAN KEUANGAN BANK SAMPAH YANG DIKELOLA OLEH YAYASAN KUMALA - Abdul Muslim (Institut Ilmu Sosial dan Manajemen Stiami, 2021)
Kumala Foundation is a form of non-profit entity, the preparation of the entity's financial statements has been regulated in the applicable reporting standard guidelines No. 45 (Guideline for SAK No. 45). The Kumala Foundation is located at Sungai Bambu road, Tanjung Priok, North Jakarta. It turns out that it has had problems in the preparation and reporting of reports because they did not comply with the applicable standards.Conducting guidance and training in preparing financial reports can be a solution to these problems, so that the Kumala Foundation can increase their financial accountability. The initial stages carried out in the guidance and training are learning activities, conducting reviews, following up on the results of reviews, and mentoring during the service period. In addition, the use of the system is expected to facilitate the process of recording financial statements